Common core curriculum world history, grades K-2 - Common Core, Inc. (San Francisco, CA Jossey-Bass/Wiley, 2014)
"The book will be a companion to the Common Core ELA Curriculum Maps, so that elementary level teachers could move easily between them and middle school ELA and social studies teachers could use them to work in close partnership. They will also incorporate the best existing state history and civics standards. Based on these standards, the maps will provide units with student objectives, readings, activities, and model lesson plans that feature the key content students need to know"--Provided by publisher.
"The Alexandria Plan"--Cover.
Includes bibliographical references and index.
Keywords: History -- Study and teaching (Elementary) -- United States